2011
DOI: 10.1080/14786419.2010.512560
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the endemic AzoreanHypericum foliosumwith otherHypericumspecies: antioxidant activity and phenolic profile

Abstract: Water extracts of Hypericum foliosum (HF) from five Azorean Islands were analysed for their antioxidant activity and total phenolic contents. The results were compared with those from medicinal Hypericum species (H. perforatum, H. androsaemum and H. undulatum) and also with Azorean green tea. HF exhibited strong scavenging activity (87-91%) and moderate inhibition of linoleic acid oxidation (56-72%), and presented no significant difference to the other studied plants; in contrast, the synthetic antioxidant but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 20 publications
4
19
0
Order By: Relevance
“…This was in line with the results on the Y TP and consisted clear evidence that differences in Y TP were reflected on the antioxidant properties of the extracts. This assumption is in accordance with previous examinations on various Hypericum species, where it was shown that extracts with higher polyphenolic load also exhibited stronger antioxidant effects [24,25]. Similar results were reported for several Hypericum taxa [26][27][28].…”
Section: Antioxidant Activitysupporting
confidence: 81%
“…This was in line with the results on the Y TP and consisted clear evidence that differences in Y TP were reflected on the antioxidant properties of the extracts. This assumption is in accordance with previous examinations on various Hypericum species, where it was shown that extracts with higher polyphenolic load also exhibited stronger antioxidant effects [24,25]. Similar results were reported for several Hypericum taxa [26][27][28].…”
Section: Antioxidant Activitysupporting
confidence: 81%
“…In the present investigation, it was observed that maximum amount of Chlorophyll a and chlorophyll b and is found in leaf and minimum in root of Tinospora cordifolia. In consonance to this Rainha et al [13] also found best result in the anatomical part of Hypericum foliosum. In contrats to this Havsteen [14], found maximum chlorophyll result in callus of Triticum aestivum and other medicinally important plants.…”
Section: Discussionsupporting
confidence: 60%
“…The antioxidant effects of hydroalcoholic SJW extracts are not surprising since they contain up to 10% flavonoids which are well-known antioxidants. Polyphenol-rich Hypericum species all display pronounced antioxidant properties [41,42]. An SJW extract specifically enriched in flavonoids (quercetin and its derivatives) quenched DPPH with an IC 50 = 10.6 μg/mL and superoxide radical with an IC 50 = 54.3 μg/mL in a concentration-dependent manner.…”
Section: Antioxidative Activitymentioning
confidence: 99%